New current relevance in Croatian: epistemic immediacy and the aorist - Stanojević, Mateusz-Milan (Array, 2011)
Croatian grammarians make conflicting claims about the Croatian aorist. Some consider it a general past tense used with perfective verbs denoting completed past while others believe that it denotes a recent past action. Both accounts focus on one of aorist uses, failing to explain some others, notably future reference. Based on a corpus study and speaker judgments, we claim that the Croatian aorist has a dual role as an aspectual and tense phenomenon expressing epistemic immediacy. We propose an analysis which contrasts an epistemically immediate virtual plane (which includes the aorist) and an epistemically distant virtual plane (which includes the Croatian perfect tense), offering a unified explanation of all aorist uses and fitting in with other Croatian and cross-Slavic data.